Escaping Shame: Mary's Dilemma and the Birthplace of Jesus - Croy, N. Clayton (Novum Testamentum, Supplements, 2022)
The only narratives of Jesus' birth locate the event in Bethlehem, but the adult Jesus is consistently associated with Nazareth. How do we reconcile these two indisputable facts? Some dismiss Bethlehem as a theologoumenon , a theological fabrication. Others insist on Bethlehem based on the census of Quirinius. In the present volume, N. Clayton Croy argues that both are wrong. Instead Jesus' birthplace was determined by the scandalous nature of Mary's pregnancy, with it being necessary for Mary and Joseph to escape the inevitable shame of an ill-timed conception and decamp to a less hostile environment. In this light, a Bethlehem-born Jesus who grew up in Nazareth should never have been considered problematic.